2006
DOI: 10.1128/jcm.01184-06
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing Antigen Cocktails for Detection ofMycobacterium bovisin Herds with Different Prevalences of Bovine Tuberculosis: ESAT6-CFP10 Mixture Shows Optimal Sensitivity and Specificity

Abstract: Bovine tuberculosis is a major problem in many countries; hence, new and better diagnostic tools are urgently needed. In this work, we have tested ESAT6, CFP10, PE13, PE5, MPB70, TB10.4, and TB27.4 for their potentials as diagnostic markers in field animals from Northern Ireland, Mexico, and Argentina, regions with low, medium, and high prevalences of bovine tuberculosis, respectively. At all three sites, ESAT6 and CFP10 were superior diagnostic antigens, while their combination performed even better at the tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
61
1
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(68 citation statements)
references
References 39 publications
3
61
1
3
Order By: Relevance
“…Previous studies have reported that Ag85A, Rv3881c, LAM, Ara 6-BSA and ESAT-6 may be useful for the serodiagnosis of pulmonary and bovine TB respectively [7][8][9][10][11]. Ag85A, ESAT-6 and TB10.4 are strongly recognized by T-cells isolated from TB patients and have been seen to induce a robust cell mediated immune response [7,12,13]. However, little is known about the diagnostic potential of these antigens in EPTB.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that Ag85A, Rv3881c, LAM, Ara 6-BSA and ESAT-6 may be useful for the serodiagnosis of pulmonary and bovine TB respectively [7][8][9][10][11]. Ag85A, ESAT-6 and TB10.4 are strongly recognized by T-cells isolated from TB patients and have been seen to induce a robust cell mediated immune response [7,12,13]. However, little is known about the diagnostic potential of these antigens in EPTB.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, la exposición a otras micobacterias o la co-infección con M. avium subsp paratuberculosis, afecta la especificidad de las pruebas basadas en el uso del PPD, incrementando el número de reacciones falsas positivas, fenómeno que puede ser evitado usando antígenos altamente inmunogénicos como ESAT-6 y CFP-10 (23) . En el presente estudio se observó que el cóctel proteico E6-C10 identificó más animales infectados que el PPDB en la prueba de IFN-γ, el 72.7 % (n= 8) de los animales se identificaron positivamente por el cóctel proteico E6-10, mientras que solo el 36.3 % (n= 4) por el PPDB (15,24) . Estas diferencias se atribuyen principalmente a la pobre definición de antígenos presentes en el PPDB, pues aunque éste proporciona una excelente sensibilidad, su especificidad es limitada, debido a que muchos antígenos presentes en el PPDB también se encuentran presentes en micobacterias ambientales.…”
Section: Cuadro 1 Bovinos Identificados En La Prueba De Ifn-γ Usandounclassified
“…Estas diferencias se atribuyen principalmente a la pobre definición de antígenos presentes en el PPDB, pues aunque éste proporciona una excelente sensibilidad, su especificidad es limitada, debido a que muchos antígenos presentes en el PPDB también se encuentran presentes en micobacterias ambientales. Por otro lado, el coctel proteico E6-C10 está formado por dos antígenos que solo están presentes en bacterias del complejo M. tuberculosis, pero están ausentes en todas las cepas de M. bovis BCG y micobacterias ambientales, por lo que la especificidad de este cóctel es mucho mayor (15,17,24) .…”
Section: Cuadro 1 Bovinos Identificados En La Prueba De Ifn-γ Usandounclassified
See 1 more Smart Citation
“…Based on previous reports of diagnosis of tuberculosis in cattle using IFN-γ assays (EsxI, Mb0143, PE5, PE13 and TB10.4) (Aagaard et al 2006, Jones et al 2010, Meikle et al 2009, the aim of the present study was to assess these recombinant proteins with respect to the ability to differentiate M. bovis sensitised and non-sensitised cattle by skin test, for further evaluation of the best antigens in infected animals.…”
Section: Introductionmentioning
confidence: 99%